CONVERSATIONAL MOVES IN ACE VENTURA MOVIE - Yaebesi Gulo; Citra Anggia Putri; Juli Rachmadani Hasibuan (State University of Medan, 2019)
This study deals with Conversational Moves in Ace Ventura Movie. The purpose of the study is to find out the moves are played by the main character of Ace Ventura movie 1st series, describing how the moves are played by the characters of Ace Ventura movie 1st series and to find out the reason why the Moves are played in the way it is. The data were analyzed based on the Structure of interaction theory by Martin (1992). The analysis showed the moves are played by the main character of Ace Ventura Movie are K1 (primary knower) 37,9 %, K2 (secondary knower) 21,07 %, K1f (primary knower follow-up) 4,64 %, K2f (secondary knower follow-up)13,6 %, A1 (primary actor) 3.2 %, A2 (secondary actor) 7,14 %, A1f (primary actor follow-up) 0,35 %, A2f (secondary actor follow-up), Da1 (delay primary actor) 0,35 %, Bch (backchannel) 0,35 %, Cl (clarification) 0,35 %, Cf (confirmation) 3,2 %, Rcf (response to confirmation) 4,64 % and Ch (challenging) 0,71 %. The moves that are played by the characters is dynamic because the speakers on that dialogue staged clarification, confirmation, back-channel and challenging move on the dialogue.Keywords: ConversationalMoves, Dynamics of Exchange.